Novel application of microdissection tungsten needle in total thyroidectomy with central neck dissection for papillary thyroid carcinoma - Zheng, Weijie; Zhu, Shan; Zhang, Yimin; Wang, Zhong; Liao, Shichong; Sun, Shengrong (Frontiers in Surgery, 2022)
Background Energy-based devices (EBD) have been popularized in thyroidectomy worldwide. Microdissection tungsten needle (MDTN) is characterized by the ultra-sharp tip providing safe and meticulous dissection with effective hemostasis. However, little study has applied MDTN in thyroidectomy. Methods This retrospective study compared clinical data of the patients who underwent total thyroidectomy (TT) plus central neck dissection (CND) using MDTN, harmonic scalpel (HS), and conventional electrocautery (CE). We assessed outcomes related to surgical efficacy and safety. The injury degree of tissue was assessed by biochemical indicators and early-stage inflammatory factors in the drainage fluid. Histological sections of the thyroid specimens were evaluated to compare levels of thermal damage by the three EBD. Results There was a significant decrease in intraoperative blood loss, operative duration, 24-hour and total drainage volume, duration of drainage, and average length of stay in the MDTN and HS group compared to the CE group, but no disparity between the MDTN group and HS group was observed. Total costs were lower utilizing MDTN although not statistically significant. The incidence of recurrent laryngeal nerve (RLN) injury was the lowest using MDTN compared to the CE (P=0.035) and HS (not significant). No statistical differences were observed among these groups regarding postoperative wound pain and infection, hypoparathyroidism, and postoperative hemorrhage. Analysis of biochemical indicators showed a lower level of hemoglobin in the MDTN and HS group than the CE group (P = 0.046 and 0.038, respectively) and less triglyceride in the HS group than the MDTN and CE group (P = 0.002 and 0.029, respectively) but no significant difference in cholesterol level in these groups. Early-stage inflammatory factors including TNF-α and IL-6 showed significantly higher concentration in the CE group than the MDTN and HS group (P <0.01). Histological sections of thyroid specimens revealed that MDTN caused the lowest degree of thermal damage followed by HS then CE. Conclusion MDTN exhibited comparable surgical efficacy and safety outcomes as HS in thyroidectomy with relatively decreased costs. Therefore, MDTN is a safe and viable alternative for hemostasis in thyroidectomy.